The integration of knowledge among academics at the International Islamic University Malaysia (IIUM) - Mamat, Arifin; Hussien, Suhailah; Ismail, Nik Ahmad Hisham; Che Haron, Sueraya (Bangladesh Institute of Islamic Thought (BIIT), Dhaka, 2015)
The International Islamic University Malaysia (IIUM) has been committed to the integration of Islamic values with the modern fields of knowledge. This study attempts to investigate academics‟ perceptions of Islamization of Knowledge (IOK), examine their practices of integration in the IIUM curriculum and establish indicators to measure the integration of knowledge. A survey distributed to a purposive sampling consisting of 306 academics from different Kulliyyahs in IIUM found that respondents have a good awareness about the integration of knowledge in IIUM. They believe that the integration of knowledge is an important mission and a unique feature of IIUM. The study reveals that respondents integrate contents of the subjects with several Islamic values. The most frequent method applied in the teaching and learning process was through exemplifications and evidence provision. However, the assessment of IOK was mostly done through classroom presentations. In addition, the study also reveals that the highest product/outcome of integration of knowledge is students‟ assignments.